Potential features of building information modelling for application of project management knowledge areas as advances modeling tools. (February 2023) - Chen, Shuzhen; Zeng, Yun; Majdi, Ali; Salameh, Anas A.; Alkhalifah, Tamim; Alturise, Fahad; Ali, H. Elhosiny
Highlights: This study focused on identification and evaluation of factors necessary for measurement of extent of application of PMKAs. Real-life situation of using PMKA in the construction industry sector is considered. Benefits of utilizing BIM technology to improve the use of PMKAs is highlighted. BIM-based sustainability, cost estimation, scheduling, and structural analysis within the context of PM assessed. Abstract: The Architecture, Engineering, and Construction (AEC) industry plays a vital role in infrastructure development and improves the socioeconomic status through employment opportunities and contributions to the gross domestic progress (GDP) of countries. Poor management causes a waste of time, money, and materials. The implementation of a suitable BIM design might aid the user in avoiding errors, speeding up and reducing the cost of the construction process. Nonetheless, there are serious shortcomings in BIM design that are inherent to project management, such as the preparation of a building execution technology project, the process of existing standards and collecting information in the building's exploitation period, and analysis of the existing situation and preparation of a building investment project. Knowledge and building information modeling technologies provide several roles and chances for achieving project objectives in a more efficient and effective manner, influencing the construction project management process. The objectives of this research are to analyze a real-life situation of using project management knowledge areas (PMKA) in the construction industry sector and the benefits and drawbacks of utilizing BIM technology as a tool to improve the use of PMKAs. The research investigates how the BIM approach may be used for project management and how knowledge could be gathered to create a BIM model, as well as the benefits of BIM-based sustainability, cost estimation, scheduling, and structural analysis within the context of PM. The main goal of this research is to find out how these techniques affect the efficiency of managing construction projects.